Land of milk and honey eaudiobook A novel. - Zhang, C Pam (Books on Tape, 2023)
NATIONAL BESTSELLER A NEW YORK TIMES NOTABLE BOOK  Finalist for the New York Public Library Young Lions Fiction Award Longlisted for the Joyce Carol Oates Award Longlisted for the Carol Shields Prize Longlisted for the Aspen Words Literary Prize NAMED A BEST BOOK OF THE YEAR BY NPR, HARPER'S BAZAAR, TOWN & COUNTRY , KIRKUS REVIEWS, ESQUIRE, ELECTRIC LITERATURE, SCIENTIFIC AMERICAN AND MORE ! “One of the most pleasurable, inventive reads of the year… fiendishly, deliciously fun."— San Francisco Chronicle "A profound exploration of human nature, the allure of pleasure and the choices we make in the face of adversity.” —NPR, "Books We Love" “It’s rare to read anything that feels this unique.” –GABRIELLE ZEVIN, New York Times bestselling author of Tomorrow and Tomorrow and Tomorrow " Land of Milk and Honey is truly exceptional."–ROXANE GAY, New York Times bestselling author of Bad Feminist “ A sharp, sensual piece of art.”–RAVEN LEILANI, New York Times bestselling author of Luster The award-winning author of How Much of These Hills Is Gold returns with a rapturous and revelatory novel about a young chef whose discovery of pleasure alters her life and, indirectly, the world A smog has spread. Food crops are rapidly disappearing. A chef escapes her dying career in a dreary city to take a job at a decadent mountaintop colony seemingly free of the world’s troubles. There, the sky is clear again. Rare ingredients abound. Her enigmatic employer and his visionary daughter have built a lush new life for the global elite, one that reawakens the chef to the pleasures of taste, touch, and her own body. In this atmosphere of hidden wonders and cool, seductive violence, the chef’s boundaries undergo a thrilling erosion. Soon she is pushed to the center of a startling attempt to reshape the world far beyond the plate. Sensuous and surprising, joyous and bitingly sharp, told in language as alluring as it is original, Land of Milk and Honey lays provocatively bare the ethics of seeking pleasure in a dying world. It is a daringly imaginative exploration of desire and deception, privilege and faith, and the roles we play to survive. Most of all, it is a love letter to food, to wild delight, and to the transformative power of a woman embracing her own appetite.